2021
DOI: 10.2196/26037
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Rural or Urban Status, Health Outcomes and Behaviors, and COVID-19 Perceptions Among Meditation App Users: Longitudinal Survey Study

Abstract: Background Rural and urban differences in health outcomes and behaviors have been well-documented, with significant rural health disparities frequently highlighted. Mobile health (mHealth) apps, such as meditation apps, are a novel method for improving health and behaviors. These apps may be a critical health promotion strategy during the COVID-19 pandemic and could potentially be used to address rural health disparities. However, limited research has assessed whether meditation app health outcomes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…There were 15 studies ( Bhuiyan et al, 2021 ; Chen et al, 2021 ; Cousijn et al, 2020 ; Dalkner et al, 2021 ; González-Sanguino et al, 2021 ; Gulliver et al, 2021 ; Han et al, 2021 ; Iovino et al, 2021 ; Johansson et al, 2021 ; López-Morales et al, 2021 ; Mergel and Schützwohl, 2021 ; Russell et al, 2021 ; Shuster et al, 2021 ; Somma et al, 2021 ; Stevenson and Wakefield, 2021 ) which reported the means of anxiety. Ten studies reported the anxiety means in two waves, two studies reported it in three waves, one study reported it in 10 waves, and one study reported it in four waves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 15 studies ( Bhuiyan et al, 2021 ; Chen et al, 2021 ; Cousijn et al, 2020 ; Dalkner et al, 2021 ; González-Sanguino et al, 2021 ; Gulliver et al, 2021 ; Han et al, 2021 ; Iovino et al, 2021 ; Johansson et al, 2021 ; López-Morales et al, 2021 ; Mergel and Schützwohl, 2021 ; Russell et al, 2021 ; Shuster et al, 2021 ; Somma et al, 2021 ; Stevenson and Wakefield, 2021 ) which reported the means of anxiety. Ten studies reported the anxiety means in two waves, two studies reported it in three waves, one study reported it in 10 waves, and one study reported it in four waves.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies reported the means of depression ( Bhuiyan et al, 2021 ; Chen et al, 2021 ; Cousijn et al, 2020 ; González-Sanguino et al, 2021 ; Gulliver et al, 2021 ; Han et al, 2021 ; Iovino et al, 2021 ; Johansson et al, 2021 ; Mergel and Schützwohl, 2021 ; Russell et al, 2021 ; Yocum et al, 2021 ). Ten studies reported the means in two waves, three in three waves, and one in 10 waves.…”
Section: Resultsmentioning
confidence: 99%
“…The difference between non-White and White people specifically in rates of infection, rather than severity of the illness once infected, might be associated with variations in protective behaviours practiced ( Breakwell et al, 2022 ). Statistics showed that non-White people were more likely than White people to report difficulty to follow public health policies enacted by the government ( Bhuiyan et al, 2021 ). The level of NPIs practice required not only protective equipment such as facemasks and disinfectant, but also the ability to stock food, water, gasoline, and medicine ( Lehberger et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Huberty and colleagues 21 examined utilization patterns amongst 12,151 paying subscribers to the Calm app and found that the sample was predominantly female (79.94%) and NL White (81.41%). Comparably, Bhuiyan and colleagues 22 examined 8,392 Calm users and found that the sample was mostly female (83.9%), NL White (91.8%), and college-educated (86.4%). However, one important potential barrier to access and utilization of meditation apps such as Calm is their cost which may limit accessibility 23 .…”
Section: Introductionmentioning
confidence: 96%